1999
DOI: 10.1212/wnl.53.5.1051
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor MRI assesses corticospinal tract damage in ALS

Abstract: The results support the use of diffusion tensor MRI in detecting pathology of the corticospinal tracts in ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
276
4
11

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(323 citation statements)
references
References 44 publications
32
276
4
11
Order By: Relevance
“…Unique imaging characteristics on magnetic resonance spectroscopy, functional magnetic resonance imaging, and 18 Ffludeoxyglucose positron emission tomography may aid in diagnosis [61][62][63][64]. Findings on diffusion tensor imaging also correlate with ALS phenotypes [59], disease severity scales, and disease duration [60].…”
Section: Retigabine: a Case Study For Innovative Als Clinical Trial Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Unique imaging characteristics on magnetic resonance spectroscopy, functional magnetic resonance imaging, and 18 Ffludeoxyglucose positron emission tomography may aid in diagnosis [61][62][63][64]. Findings on diffusion tensor imaging also correlate with ALS phenotypes [59], disease severity scales, and disease duration [60].…”
Section: Retigabine: a Case Study For Innovative Als Clinical Trial Dmentioning
confidence: 99%
“…Modern imaging modalities such as diffusion tensor imaging [59,60], magnetic resonance spectroscopy [61,62], functional magnetic resonance imaging [63], and 18 Ffludeoxyglucose positron emission tomography [64,65] are emerging as potential biomarkers of disease progression. Unique imaging characteristics on magnetic resonance spectroscopy, functional magnetic resonance imaging, and 18 Ffludeoxyglucose positron emission tomography may aid in diagnosis [61][62][63][64].…”
Section: Retigabine: a Case Study For Innovative Als Clinical Trial Dmentioning
confidence: 99%
“…These applications employ both the directional anisotropy that can be measured by DTI 4,5 as well as removal of this anisotropy through the use of the tensor trace. [6][7][8] For example, DTI is presently being explored as a research tool to study brain development, 9,10 multiple sclerosis, 11,12 amyotrophic lateral sclerosis (ALS), 13 stroke, 14,15, schizophrenia 16,17 and reading disability, 18 while trace imaging has become an essential part of clinical acute stroke assessment. [19][20][21][22] As first shown by Basser et al, 4 the diffusion ellipsoid obtained from DTI can not only provide a quantitative orientation-independent measure of diffusion anisotropy, 23,24 but also the predominant direction of water diffusion in image voxels.…”
Section: Introductionmentioning
confidence: 99%
“…The most common finding is a reduction of FA in the CST, which is thought to be due to the neuronal degeneration of UMN. Increased MD along the CST has been reported by some investigators [9,12,45,46]; however, no such changes were observed in another study [10]. In one of these studies, Sage et al [45] spatially interpolated FA and MD over the course of CST.…”
Section: Clinical Applicationmentioning
confidence: 94%
“…In the search for the UMN markers, several neuroimaging modalities, especially diffusion tensor imaging (DTI) [8][9][10][11][12][13][14][15][16], proton magnetic resonance spectroscopy ( 1 H-MRS) [14,15,[17][18][19][20], perfusion imaging [21], magnetization transfer imaging [22] (MTI) and functional magnetic resonance imaging (fMRI) [23][24][25], have been used with varying success. This article presents an overview of these neuroimaging methods and their potential roles in ALS.…”
Section: Introductionmentioning
confidence: 99%